2004
DOI: 10.1023/b:pham.0000026425.69874.8e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Modulation of the Transferrin Receptor on Brain Capillary Endothelial Cells

Abstract: The TfR is expressed on BCECs and actively endocytoses Tf, making it a suitable target for drug delivery to the bloodbrain barrier and the CNS. DFO up-regulates the TfR expression level, which may influence targeting efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…It is reported that various receptors are present on the luminal endothelial plasma membranes, including the transferring receptor, the insulin receptor, endothelial growth factors receptor, and low-density lipoprotein receptor [12,13]. Drug delivery systems which based on these receptors have been explored to deliver drugs across the BBB [14e16].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that various receptors are present on the luminal endothelial plasma membranes, including the transferring receptor, the insulin receptor, endothelial growth factors receptor, and low-density lipoprotein receptor [12,13]. Drug delivery systems which based on these receptors have been explored to deliver drugs across the BBB [14e16].…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that different receptors are present on the luminal endothelial plasma membranes, including the transferrin receptor, the insulin receptor, and the low-density lipoprotein receptor-related protein (LRP) [17,18]. Drug delivery systems based on the receptor-mediated mechanism have been explored to deliver drugs into the brain [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…One current candidate is receptors-mediated targeting via intravenous injection of ligand-conjugated drug delivery systems that target to receptors expressed on the luminal side of the BBB (2)(3)(4)(5)(6). Well-characterized BBB receptors mainly include the following: low-densities lipoprotein receptor (LDLR), transferrin receptor (7)(8)(9), epidermal growth factor receptor and insulin-like growth factor receptor (3,10). As a single-chain iron-binding glycoprotein, lactoferrin is a multifunctional protein to which several physiological roles have been attributed.…”
Section: Introductionmentioning
confidence: 99%